Geographical indications and the commercial evaluation of golden grass crafts in the Jalapão region of the state of Tocantins - Belas, Carla Arouca; Wilkinson, John (Sustainability in Debate, 2014)
This article looks at the increasing association of Geographical Indications with environmental conservation and cultural safeguards, with reference to a case study on the Indication of Origin of capim-dourado [golden grass] handicraft from the Jalapão region of Brazil. The objective is to reflect on the potential for this instrument of the Intelectual Property System as a means to protect products of sociobiodiversity produced by traditional communities. Our analysis covers the period beginning with the application process up to the first years following the concession of the GI, presenting the results achieved with respect to the commercial value of the handicraft, the producers and the preservation of the local environment. Data for this study was collected during three field trips between 2008 and 2012, involving approximately a hundred and eighty local protagonists, among them artisans, civil servants and research institutes active in the six municipalities of the Jalapão region ”“ Ponte Alta, Mateiros, São Felix, Novo Acordo, Lagoa do Tocantins and Santa Tereza. The results reveal the difficulties involved in mobilising the local society and the necessity for better integration between the actions of the various levels of government.